Childfree Phenomenon in Family Behavior: a Study of Maslahah Mursalah in Contemporary Social Context - Iqlima Amaniy Rahmatulloh (Al-Adalah: Jurnal Hukum dan Politik Islam, 2025)
The term childfree refers to individuals who deliberately choose not to have childrenâ€”a decision that has sparked critical discourse in both social and religious contexts. This study explores the underlying motivations behind the childfree decision, examines family behavior patterns among Indonesian childfree couples, and analyzes this phenomenon through the lens of maslahah al-mursalah in Islamic legal theory. Employing a qualitative method with a normative-empirical approach, this research is based on field interviews with five members of the Indonesian Childfree Community. Findings indicate that the decision is driven primarily by personal autonomy, health considerations, and economic concerns. Notably, childfree couples exhibit distinct patterns in household role distribution, conflict management, and future planning in the absence of children. From the perspective of maslahah al-mursalah, the childfree lifestyle raises complex tensions between individual choice and the foundational aims (maqÄá¹£id al-sharÄ«â€˜ah) of marriage and procreation in Islam. The study contributes to the emerging discourse on how Islamic legal reasoning can engage with evolving social behaviors in contemporary Muslim societies.